A SPH Simulation Approach using the Carreau Model for the Free Surface Flow of Adhesives - Rohler, M.; Kumar, V.; Richter, C.; Reinhart, G. (2018 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2018)
Adhesives are gaining importance in different industries, but the planning of the bonding process is subject to a high degree of uncertainty caused by the complex flow behavior of adhesives. Therefor the shear-thinning behavior which characterizes many types of adhesives is integrated into the Implicit Incompressible Smoothed Particles Hydrodynamix (IISPH) approach, which is ideally suited for free surface flow scenarios through its mesh-less characteristics. While these particle-based methods are already being used in the real-time simulation of Newtonian fluids in computer graphics, their applicability in engineering disciplines and simulation of complex fluid flows still has to be tested. The Carreau model has already been validated experimentally for accurately portraying the shear-thinning behavior of adhesives. In this work the Carreau model is integrated into the IISPH solver and the simulation results are compared to an analytical solution of the Poiseuille pipe flow. This approach can then be applied to lower the uncertainty in the early phase of manufacturing planning and for simulation-based optimization approaches involving rheological flow behavior.